ChemInform Abstract: A 2, 2′‐Bipyridine‐palladacycle Catalyzed the Coupling of Arylboronic Acids with Nitroarenes. Issue 48 (26th November 2013) - Peng, Dongpo; Yu, Ajuan; Wang, Hailei; Wu, Yangjie; Chang, Junbiao
Abstract A novel protocol using the title catalyst for the synthesis of diaryl ethers via coupling of boronic acids with nitroarenes is developed.